2015
DOI: 10.1002/pbc.25686
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin Hypersensitivity Reactions in Pediatric Low Grade Glioma Are Protocol Specific and Desensitization Shows Poor Efficacy

Abstract: Hypersensitivity reactions to carboplatin are more common in this cohort than previously reported and rates are protocol-dependent. Desensitization showed limited effectiveness in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…This difference could be due to the different patterns of desensitization used. The main variables influencing the success of re-exposure appear to be: the starting dose, the infusion rate and the number of increments (Lafay-Cousin et al, 2005; Ruggiero et al, 2013a; Dodgshun et al, 2016; Shah et al, 2016). A lower starting dose, a slow infusion, and a number of increments greater than or equal to 4, are associated with a greater probability of success.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be due to the different patterns of desensitization used. The main variables influencing the success of re-exposure appear to be: the starting dose, the infusion rate and the number of increments (Lafay-Cousin et al, 2005; Ruggiero et al, 2013a; Dodgshun et al, 2016; Shah et al, 2016). A lower starting dose, a slow infusion, and a number of increments greater than or equal to 4, are associated with a greater probability of success.…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin HSR has been described mostly in pediatric series of LGG, where the reported incidence is up to 47% depending on the schedules of administration (Lafay-Cousin et al, 2008; Dodgshun et al, 2016). …”
Section: Incidencementioning
confidence: 99%
“…Genc et al (2012) observed a frequency of 40% in their study. Recently, carboplatin hypersensitivity was documented in 47% of patients by Dodgshun et al (2016), and in the study by Shah et al (2016) of 144 children with LGG treated with carboplatin and vincristine, 56 (39%) experienced an HSR to carboplatin.…”
Section: Incidencementioning
confidence: 99%
“…4 leading to treatment withdrawal and the use of second-line drugs. Additionally, carboplatin administered in association with vincristine has been found to be a risk factor for adverse events, 5 raising the incidence to 68% of children treated. In response, carboplatin desensitization has been used with great success as an alternative to treatment withdrawal in adults, 3,6 allowing the patient to benefit from this drug.…”
mentioning
confidence: 99%
“…The evidence in children is far more limited, however, and in some cases, poorer efficacy has been reported. 5 In this manuscript, we describe the initial experience with carboplatin allergy and desensitization in a paediatric tertiary hospital in Madrid, 8 and all patients underwent skin prick (SPT) (10 mg/mL) and intradermal testing (ID) (1 and 10 mg/mL) for hypersensitivity to carboplatin as previously described. In the 2.5-year period reported, 6 of 7 (85.7%) patients receiving carboplatin had a reaction compatible with carboplatin hypersensitivity, 5 of whom were referred to the allergy department for carboplatin desensitization.…”
mentioning
confidence: 99%